Analysis of the Influence of Education Level and Competency on Organizational Commitment through Work Motivation in the Garment Sub-Sector in Serang Regency - Juariah, Siti; Nuryanto, Uli Wildan; Handayani, Yolla Sukma (University of Merdeka Malang, 2024)
This research was conducted on employees of garment companies in Serang Regency with the aim of knowing and analyzing the influence of education level on work motivation, competency on work motivation, level of education on organizational commitment, competency on organizational commitment, work motivation on organizational commitment, level of education on organizational commitment through work motivation and competence towards organizational commitment through work motivation. This research uses a quantitative method with a correlational design with a total population of 850 garment company employees in Serang Regency with sample determination using proportional techniques by multiplying the number of indicators by the lim scale so that the sample studied is 190 samples. The analysis method in this research uses regression analysis with the SmartPls statistical tool. The research results obtained from seven hypotheses, three hypotheses were rejected and four hypotheses were accepted. The conclusion of this research is that the level of education has a significant effect on organizational commitment and work motivation, competence has no effect on organizational commitment and work motivation, the level of education has a significant effect on organizational commitment through motivation. work and competence have no effect on organizational commitment through work motivation